Delivering the thinking healthy programme as a universal group intervention integrated into routine antenatal care: a randomized-controlled pilot study - BORAN, PERRAN; DÖNMEZ, MELİKE; BARIŞ, HATİCE EZGİ; ALTAŞ, ZEYNEP MEVA; HIDIROĞLU, SEYHAN; SAVE, DİLŞAD (My University, 2023)
© 2023, The Author(s).Background: Women with perinatal depression and their children are at increased risk of poor health outcomes. There is a need to implement non-stigmatizing interventions into existing health systems which reduce psychosocial distress during pregnancy and prevent perinatal depression. We adapted the WHO-endorsed Thinking Healthy Programme (THP) to be delivered universally to all women attending routine online pregnancy schools in Istanbul, Turkey. This study aimed to evaluate the feasibility and acceptability of this intervention. Methods: This mixed-methods study incorporated a two-arm pilot randomized controlled trial and qualitative evaluation of the feasibility and acceptability of the adapted THP – Brief Group version (THP-BGV) to a range of stakeholders. We recruited pregnant women at 12-30 weeks’ gestation through pregnancy schools within the University Hospital’s catchment area. Women in the intervention arm received five online sessions of the THP-BGV delivered by antenatal nurses. The intervention employed principles of cognitive behaviour therapy to provide psychoeducation, behaviour activation, problem-solving strategies and group support to participants. In the control arm, women received usual care consisting of routine online educational pregnancy classes aided by the antenatal nurses. The women were assessed for depressive symptoms with the Edinburgh Postnatal Depression Scale at baseline and 4-6 weeks post-intervention and also evaluated for anxiety, perceived social support, partner relationship, level of disability and sleep quality. In-depth interviews were conducted with women and other key stakeholders. Results: Of the 99 consecutive women referred to the pregnancy schools, 91 (91.9%) were eligible and 88 (88.8%) consented to participate in the study and were randomized. Eighty-two (83%) completed the final assessments. Our main findings were that this preventive group intervention was feasible to be integrated into routine antenatal educational classes and it was valued by the women and delivery-agents. While the study was not powered to detect differences between intervention and control conditions, we found small trends towards reduction in anxiety and depressive symptoms favoring the intervention arm. No serious adverse events were reported. Conclusions: Given the paucity of preventive interventions for perinatal depression in low and middle-income countries, a fully powered definitive randomized controlled trial of this feasible and acceptable intervention should be conducted. Trial registration: The study was registered at Clinical Trails.gov (NCT04819711) (Registration Date: 29/03/2021).
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Psikiyatri; Clinical Medicine (MED); PSYCHIATRY; Psikiyatri ve Ruh Sağlığı; Psychiatry and Mental Health; Perinatal depression; Psychological interventions; Thinking healthy program